Effect of Configuration on Mass Transfer in a Filter-press Type Electrochemical Cell - 徐红 黄卫民 邢艳 林海波 季洪海 姜梅 刘小波 甘树才 (Chinese journal of chemical engineering, 2008)
Effect of configuration （structure of electrode, interelectrode gap, positions of inlet and outlet, volume of the cell and additional nets） on mass transfer characteristic of a filter-press type electrochemical cell has been studied. The mass transfer coefficients on the electrodes were obtained by using the well-known technique based on the determination of limiting diffusion current. It is found that mass transfer coefficients with mesh electrode are greater than that of with plate electrode. Mass transfer coefficient is decreased with interelectrode gap. While interelectrode gap achieved a certain value （7 ram）, mass transfer coefficient is steady, no more declining. Mass transfer characteristic for different positions of inlet and outlet are different and dimensionless number groups correlated equations are obtained by experiment. Mass transfer characteristic is the best when inlet located on the top and outlet on the bottom of the cell respectively. While magnified the volume of the cell to eight times, mass transfer characteristic changes little. Mass transfer characteristic without nets is lower than that of with additional nets in the exit region, but higher than that of with additional nets in the entry region.